Is higher mean platelet volume an additional predictive marker of oligohydramnios and polyhydramnios? - Sibel Mutlu; Abdülkerim Yıldız; Ali Ramazan Benli; Neriman Çetin Benli (Journal of Contemporary Medicine, 2019)
Objectives: Amniotic fluid abnormalities are the leading cause of fetal morbidity and mortality. The aim of this study was to investigate whether prepartum mean platelet volume (MPV) is associated with and a predictable marker for oligohydramnios (OHA) and polyhydramnios (PHA). Materials and Methods: In this retrospective study, an examination was made of the records of patients who were monitored and gave birth at Karabuk Training and Research Hospital Gynecology and Obstetrics Clinic in 2014-2015. Patients with isolated OHA and PHA were included in the study group and those with normal amnion fluid volume (AFV) in the control group. A record was made of age, obstetric and clinical history, smoking, alcohol consumption, laboratory test results and ultrasonography reports in the third trimester of the pregnancy.Results: A total of 284 pregnant women were included in the study. The MPV levels of the OHA and PHA groups were significantly higher than those of the normal group (p=0.000). There was no significant difference was observed between the OHA and PHA groups (p=0.20). MPV gt;8.4 accurately differentiated AFV (AUC:68.8%, sensitivity:78.6%, specificity:59.1%). MPV gt;8.0 accurately differentiated OHA (AUC:67.1%, sensitivity:84.4%, specificity:50.0%). MPV gt;8.5 accurately differentiated PHA (AUC:70.2%, sensitivity:79.0%, specificity:61.4%).